The search for genetic markers in the development of bronchopulmonary pathology – the study of MLH1 (rs1799977) polymorphism of the reparation of DNA «Mismatches» - Andrushchenko, T.A.; Honcharov, S.V.; Dosenko, V.E. (Environment & Health, 2018)
В статье представлены результаты исследования полиморфизма гена MLH1 (rs1799977) у шахтёров и работников асбестоцементных заводов с профессионально обусловленной бронхолегочной патологией. Цель работы – изучить распределение частот генотипов гена MLH1 (rs1799977) у работников вредных и опасных отраслей промышленности для выявления маркеров риска развития бронхолегочной патологии. Материалы и методы. У 90 человек с бронхолегочной патологией и 124 респондентов исследования, которые работали в тех же условиях труда, но в анамнезе без заболеваний дыхательной системы, методом полимеразной цепной реакции в реальном времени изучен полиморфизм гена MLH1(rs1799977) репарации «несоответствий» ДНК. The results of the research on the polymorphism of MLH1 (rs1799977) gene in miners and workers of the asbestos cement plants with the occupationally determined respiratory pathology are presented in the article. Objective: We studied the distribution of the genotype frequencies of MLH1 (rs1799977) gene in workers of hazardous and harmful industries for the identification of the risk markers of the development of bronchopulmonary pathology. Materials and methods: With the help of polymerase chain reaction in real time, we studied the polymorphism of MLH1 (rs1799977) gene of the reparation of DNA “mismatches” in 90 patients with bronchopulmonary pathology and 124 respondents of the research, working under the same conditions, but without respiratory diseases. Results: The obtained results indicate the importance of MLH1 (rs1799977) polymorphism in the formation of bronchopulmonary pathology in certain occupational groups. MLH1•А/G genotype was associated with the risk of bronchopulmonary pathology, and MLH1•А/А genotype stimulated the resistance to the development of mentioned diseases. Conclusions: We established that genotype: heterozygotes MLH1•А/G (Р≤0.002, χ²=9.00; OR=2.32; 95%CI: 1.29-4.21) associated with the development of bronchopulmonary pathology and genotype: dominant homozygotes MLH1•А/А (Р≤0.003, χ²=8.73; OR=0.43; 95% CI: 0.24-0.79) probably contributed to the resistance of the development of these diseases.